A new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Langkawi Island, Malaysia - Takaoka, H.; Sofian-Azirun, Mohd; Yacob, Z. (2013)
A new black fly species, Simulium (Gomphostilbia) langkawiense, is described based on adult female, adult male, pupal, and larval specimens collected from Langkawi Island, Malaysia. This new species is similar in the configuration of the pupal gill to Simulium (Gomphostilbia) gombakense Takaoka & Davies, 1995, originally described from Peninsular Malaysia, but differs from the latter species by the female genital fork with an anterolaterally angulated plate on each arm, the female tarsal claw tooth shorter than one half of the claw, the small number of male upper-eye large facets, the ventral plate with its ventral margin nearly flat in the middle when viewed posteriorly, and the inflated structure of the pupal gill with a less produced middle portion (width of middle inflated portion: length of inflated structure = 0.24). Taxonomic notes are also given to separate this new species from two other related species from Nepal and India. This represents another example of a unique species of black fly on one of the continental islands of Peninsular Malaysia.